y=6(3)-39

Simple and best practice solution for y=6(3)-39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=6(3)-39 equation:


y=6(3)-39

We simplify the equation to the form, which is simple to understand
y=6(3)-39

Reorder the terms in parentheses
y=+(+18)-39

Remove unnecessary parentheses
+y=+18-39

We move all terms containing y to the left and all other terms to the right.
+1y=+18-39

We simplify left and right side of the equation.
+1y=-21

We divide both sides of the equation by 1 to get y.
y=-21

See similar equations:

| x-3=-5x-9 | | (2k+3)(5k+1)= | | 9+5w-1w=12-6w | | 10m^2-53m+36=0 | | 7x+2x-3x=3(x-8) | | y=2(3)-25 | | .01(900-30x)=9.8x+400 | | 3x^2=288x^2 | | 9+5w-14x=12-6w | | y=3(3)-22 | | 5(2x+6)=4(-5-2x)3x | | x-4=-4x-2 | | 4m-19-11=70 | | 6r-18=30 | | 18=-3y-12 | | 87-x=136 | | 3/8=r2/3 | | (3w+5x-7)(w+7x)= | | X+5=x+11 | | 5x+4x+8-2x-8= | | 4/17 | | y=-5(3)+17 | | 2=(4/p) | | 4(6-4+6)= | | 5x-4=4-4x | | 8+8x=4x+24 | | 3(2z+2.5)-2(2-1)=78 | | (2/3)(-11/8) | | -48+3m=-6(1-4m) | | ln(4x^2-100)-ln(x-2)=0 | | -2p+3=8p-7 | | 9c-3=15c+15 |

Equations solver categories